Factors Associated with Premarital Sexual Behavior in Adolescents - Nur Fauziah, Ani; Maesaroh, Siti; Nur Rokhmatun, Puji; Sulistyorini, Etik (Gaster, 2025)
Background: The increasing number of marriage annulments in cases of illegitimate child pregnancies is an iceberg phenomenon. Therefore, this is considered an emergency. Objective : This study aims to determine the factors related to premarital sexual behavior in adolescents. This type of research is cross-sectional analytic. The independent variables are age, education level, occupation, knowledge of premarital sexual behavior, the role of parents, the role of information media and peer influence, while the dependent variable is premarital sexual behavior. Methods: The study subjects were 48 adolescents in Karangkendal Village, Tamansari District, Boyolali Regency in June 2023. Bivariate data analysis used the chi-square test and multivariate data analysis used multiple linear regression, while data processing used the IBM SPSS 25 program. Results : The results of the study obtained an R value of 0.569, so that the results obtained showed a relationship between age, education, occupation, knowledge of premarital sex, media exposure, parental roles, and peer influence on premarital sexual behavior in adolescents. The R square value was 32.4%, Conclusion: There is an influence of age, level of education, occupation, knowledge about premarital sex, media exposure, parental role and peer influence on premarital sexual behavior in adolescents, while other factors cause the rest.